2021
DOI: 10.1186/s12876-021-01828-z
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in liver transplantation indications in Saudi Arabia: from hepatitis C virus infection to nonalcoholic fatty liver disease

Abstract: Background Several trend analyses on liver transplantation (LT) indications have been published in the U.S. and in other countries, but there are limited data on LT indication trends in Saudi Arabia (SA), especially since the availability of direct-acting antivirals (DAAs) treatment for hepatitis C virus (HCV). This study aimed to analyze trends in the frequency of LT indications among LT recipients in SA over a 19-year period and examine associations between etiologic-specific trends and clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…However, it has been shown that PSC and AIH cirrhosis had a low proportion among patients who underwent LT in the country. 17 In contrast, another study reported that the proportion of alcoholic cirrhosis, the third leading indication for LT, and NASH cirrhosis increased between 2000 and 2015, while the proportion of HCV cirrhosis decreased during the study period in the United States. 18 In accordance with our study, an analysis of data collected from UK and US national liver transplant registries between 1995 and 2014 declared that PSC is the leading indication for LT among patients with autoimmune liver diseases, including PSC, PBC, and AIH.…”
Section: Discussionmentioning
confidence: 92%
“…However, it has been shown that PSC and AIH cirrhosis had a low proportion among patients who underwent LT in the country. 17 In contrast, another study reported that the proportion of alcoholic cirrhosis, the third leading indication for LT, and NASH cirrhosis increased between 2000 and 2015, while the proportion of HCV cirrhosis decreased during the study period in the United States. 18 In accordance with our study, an analysis of data collected from UK and US national liver transplant registries between 1995 and 2014 declared that PSC is the leading indication for LT among patients with autoimmune liver diseases, including PSC, PBC, and AIH.…”
Section: Discussionmentioning
confidence: 92%
“…Our study was limited by the availability of data, and we used data from outside of SA for certain microsimulation modules. We identified a need for more up-to-date, national, and regionally representative data on obesity incidence and prevalence, as well as specific liver diseases such as NAFLD, which are on the rise in SA [ 19 ]. More frequent, high-quality data will enable more detailed modelling of the associations between obesity and NCDs in SA and more accurate projections of the economic and health burden from NCDs.…”
Section: Discussionmentioning
confidence: 99%
“…A more serious NAFLD variantnon-alcoholic steatohepatitis (NASH)is linked to advanced liver fibrosis, cirrhosis, and liver cancer [18]. NASH has overtaken hepatitis C virus as the most common indication for liver transplants in SA [19]. The health and economic burden of T2DM, liver disease, and liver cancer could be dramatically reduced with effective obesity policies and lifestyle interventions [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In SA, NAFLD has overtaken hepatitis-induced liver disease as the main indication for liver transplants [ 12 ]. Challenges in diagnosis and surveillance of NAFLD and NASH, including patient unawareness or neglect, missed diagnosis, lack of or absence of symptoms, mean that estimates of the population burden of obesity-related liver disease are limited to a few studies [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%